Corporate Value from the Perspective of Sustainable Development Research: A SciMAT Bibliometric Analysis - Błach, Joanna; Gorzeń-Mitka, Iwona (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2025)
Objective: This paper aims to synthesise the extant literature on corporate value in the context of sustainable development research over the past two decades with a focus on 2004–2023.Research Design & Methods: The study uses various bibliometric analysis methods: citation analysis, keyword co-occurrence mapping, analysis of bibliographic productivity and impact indicators. The bibliometric analysis software SciMAT was used to develop visualisations of the identified research trends. Following the methodological rigour of PRISMA, the analysis covers 329 publications from the Scopus database from 2004 to 2023.Findings: Results illustrate the evolution of corporate value research in the context of sustainable development, its increasing importance, interactions, stability and changes in the research network. Recent topics include sustainability reporting as one of the key determinants of corporate value and the role of innovation in sustainable business models. Potential areas of research include sustainability reporting, corporate governance, and R&D. A lack of research on sectors other than manufacturing and regions other than Central Europe is noted, suggesting interesting avenues for future investigation.Implications / Recommendations: This study can be used as a reference point for researchers investigating the determinants of corporate value within the context of sustainability. It identifies key areas where further action is needed to raise managers’ awareness and understanding of the critical relationship between corporate value and sustainability issues.Contribution: The presented literature review is one of the first such comprehensive studies in this area to use big data analytics. It identifies evolutionary changes, recent trends and outlines new directions for future research.